Determination of structural properties of red seraya plywood using eurocodes compliant testing method / Tsen Shuk Fun - Tsen, Shuk Fun (2013)
Bending strength (MOR) and modulus of elasticity (MOE) are the primary criteria to evaluate the mechanical properties of structural plywood. Ever since structural plywood was introduced, numerous studies have been conducted on its mechanical properties. Most of these studies were conducted on temperate timber species, less focus has been given to tropical timber species. Red seraya (Shorea spp.) was chosen to be studied in depth because it is found in abundance in East Malaysia and has been one of the largest sawnwood species exported by Malaysia. To address this issue, a comprehensive study on the mechanical properties of red seraya structural plywood was carried out. Using test specimens of 4 mm to 15 mm thickness, the MOR and MOE of red seraya structural plywood were compared with the published values of better known structural plywood species – birch (Betula pendula) and spruce (Picea abies). They were chosen because they are two of the most important species in structural plywood industries. Furthermore, destructive and non-destructive bending tests were conducted to assess the mechanical properties of red seraya structural plywood. The MOR and MOE obtained from the Eurocode standards, EN 310 three-point bending and EN 789 four-point bending test, were compared and correlations between their values were established. In addition, finite element (FE) analysis was carried out to predict the mechanical properties of red seraya structural plywood. The test results determined from EN 789 showed that, red seraya plywood maximum MOR was 38% lower than birch plywood but was 39% higher than spruce plywood. Meantime, the maximum MOE of red seraya plywood was 25% lower than iii birch plywood but about the same when compared to spruce plywood. In addition, it was found that the maximum MOR and MOE of red seraya plywood determined using EN 310 were respectively 24% higher and 42% lower compared to the results obtained from EN 789. The linear regressions developed in this study can be used to predict the MOR and MOE values between the test methods. It was found that the MOR and MOE of EN 789 had a moderately strong correlation with those obtained by EN 310. Simple FE models were proposed to predict the MOR and MOE proportionately for EN 789 and EN 310. The MOR determined by FE model for EN 310 and EN 789 gave maximum values that were respectively 23% and 16% higher than the results obtained experimentally. Similarly, the MOE determined by FE model for EN 310 and EN 789 gave maximum values that were respectively 39% and 14% higher than those obtained experimentally. Correlations between FE analysis and experimental results were established to study the feasibility of using FE analysis to predict the mechanical properties of structural plywood. The FE analysis showed satisfactory agreement with the experimental results, especially for EN 789. This research showed that red seraya structural plywood is comparable to spruce plywood but gave lower values when compared with birch plywood. In addition, the mechanical properties of red seraya structural plywood determined using EN 310 and EN 789 were significantly different.